β-adrenergic stimulation controls the expression of a thioesterase specific for very-long-chain fatty acids in perfused hearts - Neuman, Maria Isabel (2002)
Arachidonic acid is not freely stored in the cells. A number of different pathways for the mobilization of this compound have been proposed, including a novel mechanism that involves the release of arachidonic acid from arachidonoyl-CoA by a thioesterase with substrate specificity for very-long-chain fatty acids. In rat heart, the acyl-CoA thioesterase activity can be regulated by a mechanism that involves β-adrenoceptors. In this paper we demonstrate that β-adrenergic agonists also regulate the acyl-CoA thioesterase mRNA levels. Isoproterenol (10-7) a concentration known to exert physiological responses - increases in a time-dependent manner the acyl-CoA thioesterase mRNA levels, an effect blocked by a specific β-adrenoceptor antagonist. In addition, our results show that cAMP is involved in this process. The acyl-CoA thioesterase mRNA levels are also increased by fasting, but not by di(2-ethylhexyl)phthalate, a peroxisome proliferator. These results may suggest the existence of a β-adrenoceptor-activated regulatory pathway for arachidonic acid release in cardiac tissue. © 2002 Elsevier Science (USA). All rights reserved.